Acupuncture modulates the microbiota-gut-brain axis: a new strategy for Parkinson’s disease treatment - Zang, Zimo; Yang, Fang; Qu, Liang; Ge, Minghui; Tong, Liang; Xue, Lihui; Sun, Xiuye; Hai, Ying (Frontiers in Aging Neuroscience, 2025)
Parkinson’s disease is a relatively common neurodegenerative disorder in clinical practice, and its prevalence is increasing worldwide. It not only causes patients to have movement disorders such as tremors and delayed initiation but also makes them suffer from olfactory disorders, gastrointestinal disorders, insomnia and other symptoms, which imposes a heavy burden on both patients and their families. In recent years, some scholars believe that the gut-brain axis may be the key to revealing the pathogenesis of Parkinson’s disease. The changes in intestinal flora, or bacterial infections and oxidative stress, lead to abnormal aggregation of alpha-synuclein and formation of neurotoxic Lewy bodies, which are transmitted to the central nervous system via the vagus nerve, thus causing Parkinson’s disease. A large number of evidence-based studies have shown that acupuncture is effective in treating motor disorders and non-motor symptoms such as constipation, neuropsychiatric symptoms, and dysphagia symptoms in Parkinson’s disease, also this treatment is safe. However, its mechanism remains unclear. Acupuncture may affect the gut-brain axis and treat PD by improving intestinal flora imbalance, interfering with the expression of alpha-synuclein protecting neurological function, reducing imflammation, and influencing glial cells, etc. Therefore, the aim of this review is to elucidate the pathogenesis of PD from the perspective of neural, immune, and metabolic signaling pathways of the microbiota-gut-brain axis. In addition, this paper integrates the mechanism of acupuncture treatment with the pathogenesis of PD for the first time and to provide potential new strategies for its treatment.